Why Pedestrianization Projects in Iran Fail, Case Study: 17 Shahrivar Street in Tehran - Mohammad javad nouri; Iraj Etessam (صفه)
The first pedestrianized streets seem to have appeared in cities during the 1940s and 1950s along with concerns of conservation and improvement of historic fabrics. With the domination of cars and their accompanying problems in urban life, pedestrianization movements started all over the world in 1960s-1970s which are still continued. Although after a slight delay, the movement has reached Iran and there are many cities in which urban streets are turned into pedestrian areas. However, there are some cases which eventually fail at this. This paper is in search of the reasons for such failures, examining 17 Shahrivar Street in Tehran as a case study. In order to determine the reasons for the failure of this project, it has been analyzed from both a substantive (spatial quality of the pedestrian area) and a procedural dimension (the process of project implementation). The research uses grounded theory methodology, in which semi-structured interviews were carried out with 15 respondents from local tradespersons, local residents, and peddlers. Next, steps were taken to identify codes, categories, major categories, and the core category in both the substantive and the procedural dimensions of the project according to the interviews and the project documents. Codes in the substantive dimension indicate environmental qualities of the pedestrian area while codes in the procedural dimension indicate ethical values during the four-stage life cycle of the project. The core categories of the procedural and substantive dimensions are “lack of shared understanding of the project life cycle in the urban management system” and “insufficient innovation in the planning and design of the pedestrian area” respectively, which together, constitute the main reasons for the failure of the 17 Shahrivar Street project.